Wave-induced loss of ultra-relativistic electrons in the Van Allen radiation belts - Yuri Y. Shprits; Alexander Y. Drozdov; Maria Spasojevic; Adam C. Kellerman; Maria E. Usanova; Mark J. Engebretson; Oleksiy V. Agapitov; Irina S. Zhelavskaya; Tero J. Raita; Harlan E. Spence; Daniel N. Baker; Hui Zhu; et al. (Nature Communications, 2016)
The processes that lead to losses of highly energetic particles from Earth’s radiation belts remain poorly understood. Here the authors compare observations and models of a 2013 event to show that electromagnetic ioncyclotron waves provide the dominant loss mechanism at ultra-relativistic energies.